Swallowing Assessment in a Pediatric Case of Allan–Herndon–Dudley Syndrome (MCT8 Deficiency): Advanced Insights into Dysphagia via Flexible Endoscopic Evaluation of Swallowing - Scholtes, Nina; Jelesch, Evelyn; Diesener, Paul; Stoffels, Johannes C.; Völkl, Thomas M.K. (Neuropediatrics, 2025)
Patients with MCT8 deficiency often present with underweight and are prone to frequent pulmonary infections, including aspiration pneumonia. Despite commonly reported swallowing difficulties in this population, specific dysphagia symptoms have not been well-documented. We conducted a flexible endoscopic evaluation of swallowing (FEES) on a young boy diagnosed with MCT8 deficiency, who exhibited recurrent pulmonary infections and failed to achieve substantial weight gain despite an oral energy intake appropriate for his age and height. The FEES revealed generally weakened swallowing mechanisms, characterized by prolonged swallow and cough sequences, along with penetration and aspiration of both fluid and semi-solid test boluses. Given the considerable effort associated with oral intake, we hypothesize that dysphagia contributes to his underweight status, alongside peripheral thyrotoxicosis. In conclusion, FEES proved to be an invaluable tool in identifying underlying swallowing impairments and assessing the need for gastrostomy in this patient. For MCT8 deficiency, patients presenting with underweight, frequent pulmonary infections, and swallowing difficulties, it is recommended that diagnostic evaluations include FEES to thoroughly assess their swallowing function and airway protection.
Keywords: MCT8; dysphagia; swallowing; aspiration; FEES